2021
DOI: 10.15537/smj.2021.42.9.20210281
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor for 31-day unplanned readmission to hospital in patients with pulmonary tuberculosis in China

Abstract: Objectives: To evaluate risk factors associated with 31-day unplanned readmission(s) for pulmonary tuberculosis (TB) in China.Methods: This retrospective study enrolled patients (age, >14 years) with pulmonary TB who experienced 31-day unplanned readmissions to a specialized hospital for TB between January 2018 and December 2019. For each confirmed readmission, 2 control subjects were randomly selected from among patients with pulmonary Original Article TB but did not experience an unplanned readmission within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…This study was a retrospective study on patients with recurrent pulmonary TB. In this research, the rate of unplanned readmission of patients with pulmonary TB within 30 days after discharge was 5.2%, lower than that reported by Jing et al (5.91%) [17]. The present study showed significant associations among unplanned readmissions in terms of gender, age, place of residence, smoking, COPD, viral hepatitis, drug abuse, non-standard treatment, adverse drug reactions, and noncompliance with hospital discharge.…”
Section: Discussioncontrasting
confidence: 69%
“…This study was a retrospective study on patients with recurrent pulmonary TB. In this research, the rate of unplanned readmission of patients with pulmonary TB within 30 days after discharge was 5.2%, lower than that reported by Jing et al (5.91%) [17]. The present study showed significant associations among unplanned readmissions in terms of gender, age, place of residence, smoking, COPD, viral hepatitis, drug abuse, non-standard treatment, adverse drug reactions, and noncompliance with hospital discharge.…”
Section: Discussioncontrasting
confidence: 69%
“…For treatment nonadherence, effect measures were extracted from seven of eight included studies, 33 , 77 , 82 , 113 , 116 , 133 , 135 , 136 all reporting increased risk associated with tobacco use, and one also reporting increased risk associated with ST use. 77 Disease severity was indicated by risk of hospitalization or cavitation in five included studies, 32 , 126 , 128 , 130 , 143 and all reported increased risk with tobacco use. Finally, one case-control study reported an increased risk of drug resistance developing with tobacco use compared with no tobacco use.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the prolonged hospital stay was higher among people living in rural areas than those living in urban areas. Other studies have shown people living in rural areas are more prone to infections, adverse health outcomes and higher admission rates due to a lack of awareness of disease prevention [25], poverty, poor socioeconomic and poor dietary habits [26]. This could be true in Bhutan because the rural population has fewer resources to obtain health education.…”
Section: Discussionmentioning
confidence: 99%